Pengaruh Transformational Leadership Terhadap Employee Porformance Pada Lembaga Pemasyarakatan Narkotika Kelas Iib Purwokerto - Bagus Indra Gunawan; Padmono Wibowo (JOURNAL SAINS STUDENT RESEARCH, 2023)
This study aims to analyze the relationship between transformational leadership and employee performance at the Class IIB Narcotics Correctional Institution Purwokerto. The main issues studied were the effects of transformational leadership style on improving employee performance. This study uses a quantitative approach method in which the data collection technique uses a questionnaire through a google form distributed to respondents consisting of employees of the Purwokerto Narcotics Correctional Facility. The research sample consisted of 33 respondents who were randomly selected. Based on the results of the study it can be concluded that transformational leadership has a positive and significant relationship with employee performance. Effective transformational leadership can improve employee performance at Purwokerto Narcotics Prison